2015
DOI: 10.1371/journal.pone.0128325
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Personal and Family Factors in the Persistence of Attention Deficit Hyperactivity Disorder: Results of a Prospective Follow-Up Study in Childhood

Abstract: ObjectivesTo study the course of ADHD during childhood and analyze possible personal and family predictor variables of the results.MethodSixty-one children with ADHD who were between 6 and 12 years old at the baseline assessment were evaluated 30 months later (mean age at baseline: 8.70 ± 1.97; mean age at follow-up: 10.98 ± 2.19). Status of ADHD in follow-up was identified as persistent (met DSM-IV-TR criteria according to parents’ and teachers’ ratings), contextually persistent (met ADHD criteria according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 62 publications
1
17
2
Order By: Relevance
“…According to a recent study, high parenting stress but not parenting/discipline style distinguished persisters and remitters. 12 In contrast to this study, we found a good parental disciplining style to protect against adult ADHD symptom persistence. However, neither marital problems nor parenting styles were associated with adult ADHD symptoms when using continuous scores as outcomes or using impairment ratings in addition to symptom count to define ‘persistence’.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…According to a recent study, high parenting stress but not parenting/discipline style distinguished persisters and remitters. 12 In contrast to this study, we found a good parental disciplining style to protect against adult ADHD symptom persistence. However, neither marital problems nor parenting styles were associated with adult ADHD symptoms when using continuous scores as outcomes or using impairment ratings in addition to symptom count to define ‘persistence’.…”
Section: Discussioncontrasting
confidence: 99%
“…Persisters are more likely than desisters to have comorbid oppositional, addiction, anxiety and depression problems as well as functioning difficulties in social, educational, emotional and cognitive domains. 812 It is not understood whether such differences are cause, effect, or simply associated through some third factor. More importantly, it is not known if such differences in functioning are already present at an early age and predate the divergence in ADHD symptom profiles into persistent and desistent types.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Beside chronic nature of this disease, a high rate of comorbidity is the other worrying issue that is a feature of ADHD (Miranda, Colomer, Fernández, Presentación, & Roselló, 2015).…”
Section: Introductionmentioning
confidence: 99%